Internet users’ utopian/dystopian imaginaries of society in the digital age: Theorizing critical digital literacy and civic engagement - Polizzi, Gianfranco (New media & society, 2023)
This article proposes a theoretical framework for how critical digital literacy, conceptualized as incorporating Internet users’ utopian/dystopian imaginaries of society in the digital age, facilitates civic engagement. To do so, after reviewing media literacy research, it draws on utopian studies and political theory to frame utopian thinking as relying dialectically on utopianism and dystopianism. Conceptualizing critical digital literacy as incorporating utopianism/dystopianism prescribes that constructing and deploying an understanding of the Internet’s civic potentials and limitations is crucial to pursuing civic opportunities. The framework proposed, which has implications for media literacy research and practice, allows us to (1) disentangle users’ imaginaries of civic life from their imaginaries of the Internet, (2) resist the collapse of critical digital literacy into civic engagement that is understood as inherently progressive, and (3) problematize polarizing conclusions about users’ interpretations of the Internet as either crucial or detrimental to their online engagement.